Does anti-p53 antibody status predict for clinical outcomes in metastatic colorectal cancer patients treated with fluoropyrimidine, oxaliplatin, plus bevacizumab as first-line chemotherapy?. Issue 1 (December 2015) - Osumi, Hiroki; Shinozaki, Eiji; Suenaga, Mitsukuni; Kumekawa, Yosuke; Ogura, Mariko; Ozaka, Masato; Matsusaka, Satoshi; Chin, Keisho; Yamamoto, Noriko; Mizunuma, Nobuyuki
Abstract Background TP53 gene mutation is widely known as one of the determinants of impaired chemosensitivity. p53 is a tumor-suppressor protein in humans encoded by theTP53 gene. Some studies have shown thatTP53 gene mutation and accumulation of the p53 protein are closely related with serum anti-p53 antibody positivity. This study aimed to evaluate the predictive significance of the serum p53 antibody status in metastatic colorectal cancer (mCRC) patients treated with fluoropyrimidine, oxaliplatin, plus bevacizumab as first-line chemotherapy. Methods Ninety patients treated with fluoropyrimidine, oxaliplatin plus bevacizumab as first-line chemotherapy were enrolled, including 70 whoseKRAS genotype was revealed at the beginning of treatment. Before chemotherapy initiation, the serum p53 antibody level was quantified by enzyme-linked immunosorbent assay using MESACUP® anti-p53 test kits. The cutoff value for positivity was 1.3 U/mL, as calculated previously. TheKRAS genotype of the tumor samples was analyzed using the Luminex® assay. Results Overall response rates of Response Evaluation Criteria in Solid Tumors criteria were 77.7 % (42/54) in anti-p53–negative patients and 69.4 % (25/36) in anti-p53–positive patients. The odds ratio was 1.07. Median overall survival was 36.1 months in the anti-p53–positive patients, and not available in the anti-p53–negative patients (hazard ratio, 0.81; 95 % confidence interval, 0.37–1.77;P  = 0.61). The corresponding values for median progression-free survival were 13.3 months and 14.6 months (hazard ratio, 0.69; 95 % confidence interval, 0.41–1.17;P  = 0.17), respectively. Conclusions Serum anti-p53 antibody positivity did not predict chemoresistance in mCRC treated with fluoropyrimidine, oxaliplatin, plus bevacizumab as first-line chemotherapy.